Prevalence of nocturnal enuresis among children of Aseer region in Saudi Arabia - Abdulaziz Alamri; Vinod Prem Singh; Mishari H M Alshyarba; Alahmari Abdullah; Meshal Ogran; Abdullah Alsuayri; Amal Al-Amri; Tarique Hussain Ashraf; Fahad Alyami; Mohammed Sharaf Alshahrani (Urology Annals, 2024)
Introduction: Nocturnal enuresis (NE) in children is a very common problem managed in pediatric urology. In this study, we present the prevalence of NE in children in Aseer region in Saudi Arabia. Methodology: This study was conducted as a descriptive cross-sectional survey to estimate the prevalence of NE among 555 Saudi children aged 5–15 years in Aseer region in Saudi Arabia. Data collection was done through a questionnaire, which included questions on sociodemographic data, personal knowledge, enuresis-related characteristics, risk factors, and management modalities. Results: This study identified a prevalence of enuresis of 24% of the study population, most of whom were boys. The majority of the parents had a high educational level. Clinical characteristics of the study population showed: 9% have a family history of NE, 2.2% have a history of neurological disorder, 10.0% have a history of urinary tract infections, 66.8% have associated daytime urgency, 67% have urine-holding behavior, and 19.5% have associated daytime enuresis of the study population. Conclusion: Our study found that 24% of children in the Aseer region in Saudi Arabia have NE. Our study finding helps us to understand the prevalence of NE in Aseer region in Saudi Arabia, and this can be applied to other regions in the kingdom. Furthermore, this finding helps us to understand the need to raise awareness in the community about NE and the need to educate the nonpediatric urologist health-care provider about the best management practice for NE.